The Total Energy Efficiency Index for machine tools. (1st May 2016) - Schudeleit, Timo; Züst, Simon; Weiss, Lukas; Wegener, Konrad
Abstract: Energy efﬁciency in industries is one of the dominating challenges of the 21st century. Since the release of the eco-design directive 2005/32/EC in 2005, great research effort has been spent on the energy efficiency assessment for energy using products. The ISO (International Organization for Standardization) standardization body (ISO/TC 39 WG 12) currently works on the ISO 14955 series in order to enable the assessment of energy efficient design of machine tools. A missing piece for completion of the ISO 14955 series is a metric to quantify the design of machine tools regarding energy efficiency based on the respective assembly of components. The metric needs to take into account each machine tool components' efficiency and the need-oriented utilization in combination with the other components while referring to efficiency limits. However, a state of the art review reveals that none of the existing metrics is feasible to adequately match this goal. This paper presents a metric that matches all these criteria to promote the development of the ISO 14955 series. The applicability of the metric is proven in a practical case study on a turning machine. Highlights: Study for pushing forward the standardization work on the ISO 14955 series. Review of existing energy efficiency indicators regarding three basic strategies to foster sustainability. Development of a metric comprising the three basic strategies to foster sustainability. Metric application for quantifying the energy efficiency of a turning machine.